How Would Covid-19 Survivors Travel?: A Study on Travelling Behavior Bali Domestic Tourists - Putu Gde Arie Yudhistira; I Wayan Bagus Purnama Sidi; Theresia Verina Rosari Bei; I Dewa Ayu Nindya Prathiwi S (Jurnal Kawistara, 2022)
This study aims to discover how tourists whose background as COVID-19 survivors and the perceived health-related risks when traveling and how it affects their travel behavior in the future. This research is motivated by the lack of study on tourist traveling behavior, particularly from a specific segment of respondents. These respondents are tourists who were diagnosed positive for COVID-19 and have already recovered from it and are currently on vacation in two areas in Bali, Denpasar, and Badung. Sampling in this study is based on a purposive convenience sampling method through questionnaires distributed online and offline. In addition, The author uses Roscoe's Theory as a baseline in obtaining the minimum number of respondents, where a total of 100 respondents were gathered on the field. The author used multiple linear regression analysis to analyze the data collected from this research. The results of this study found that: (1) perceived health risks do not have a significant influence on future travel behavior; (2) tourists’ conditions as COVID-19 survivors have a significant influence on future travel behavior; and (3) simultaneously, health risks and tourists’ conditions as COVID-19 survivors influence future travel behavior. This study concludes that reducing perceived health risks and improving the health conditions of tourists as Covid-19 Survivors will improve their travel behavior in the future. The limitations of this study can also be used as suggestions for further research.